Toxicological evaluation of Moringa oleifera Lam seeds and leaves in Wistar rats (2016)
Miracle tree (Moringa oleifera) as it is popularly called, has been found useful both medicinally and economically. Its consumption both in the raw and as processed preparations has increased a great deal thus making the fast growing plant a highly valued and cultivated one in the tropics and sub-tropics. There is however, little reference to its toxicity profile and evaluation. Hence, this study evaluated the toxicity profiles of the leaves and seeds of M. oleifera and the corresponding effects on vital organs of Wistar rats using the biochemical, heamatological and histopathological indices. Daily doses of 100, 200, 400 and 1000 mg/kg body weight of crude methanol extracts of M. oleifera leaves and seeds were administered orally to 8 groups of 5 rats per group each for 28 days. A control group of 5 rats was also included in the experiment. Heamatological, biochemical and histopathological indices were evaluated by standard methods. Data were analyzed using one way analysis of variance and statistically significant difference was considered at p <0.05, p<0.01 and p<0.001. Histopatho- logical changes were observed in the heart, liver, lungs, spleen and kidneys of rats treated with the extracts at all doses tested. Some other physical changes like agitation, confusion and disorientation were observed at the highest dose tested (1000 mg/kg) of the seed extract. A significant increase (p<0.05) in neutrophil, white blood cell (WBC) and platelet were observed. However, a significant decrease in aspartate amino transferase (AST), alanine amino transaminase (ALT), alkaline phosphatase, (ALP) was also observed. The results suggest that the leaf and seed extracts of M. oleifera could boost immunity and offer hepatoprotective effects.